The Effects of Governmental Protected Areas and Social Initiatives for Land Protection on the Conservation of Mexican Amphibians - Ochoa-Ochoa, Leticia; Urbina-Cardona, J. Nicolás; Vázquez, Luis-Bernardo; Flores-Villela, Oscar; Bezaury-Creel, Juan (PLOS ONE, 2009)
Traditionally, biodiversity conservation gap analyses have been focused on governmental protected areas (PAs). However, an increasing number of social initiatives in conservation (SICs) are promoting a new perspective for analysis. SICs include all of the efforts that society implements to conserve biodiversity, such as land protection, from private reserves to community zoning plans some of which have generated community-protected areas. This is the first attempt to analyze the status of conservation in Latin America when some of these social initiatives are included. The analyses were focused on amphibians because they are one of the most threatened groups worldwide. Mexico is not an exception, where more than 60% of its amphibians are endemic. We used a niche model approach to map the potential and real geographical distribution (extracting the transformed areas) of the endemic amphibians. Based on remnant distribution, all the species have suffered some degree of loss, but 36 species have lost more than 50% of their potential distribution. For 50 micro-endemic species we could not model their potential distribution range due to the small number of records per species, therefore the analyses were performed using these records directly. We then evaluated the efficiency of the existing set of governmental protected areas and established the contribution of social initiatives (private and community) for land protection for amphibian conservation. We found that most of the species have some proportion of their potential ecological niche distribution protected, but 20% are not protected at all within governmental PAs. 73% of endemic and 26% of micro-endemic amphibians are represented within SICs. However, 30 micro-endemic species are not represented within either governmental PAs or SICs. This study shows how the role of land conservation through social initiatives is therefore becoming a crucial element for an important number of species not protected by governmental PAs.